2015
DOI: 10.1186/s12886-015-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

One-year outcomes of small-incision lenticule extraction (SMILE): mild to moderate myopia vs. high myopia

Abstract: BackgroundThe purpose of this study was to compare the refractive outcomes of small incision lenticule extraction (SMILE) in high-myopic patients with those of mild- to moderate-myopic patients.MethodsThis study included 183 eyes of 92 myopic patients treated with SMILE using a VisuMax 500-kHz femtosecond laser. Treated eyes were divided into two groups, according to the preoperative spherical equivalent (SE): mild to moderate myopia (A group, <−6.0 D) and high myopia (B group, ≥ − 6.0 D). Follow-up visits wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 19 publications
5
36
2
1
Order By: Relevance
“…Early evidence suggests that the SMILE procedure is safe . Intra‐operative complications may occur; however, these are not likely to be sight threatening.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early evidence suggests that the SMILE procedure is safe . Intra‐operative complications may occur; however, these are not likely to be sight threatening.…”
Section: Complicationsmentioning
confidence: 99%
“…Early evidence suggests that the SMILE procedure is safe. 2,5,6,11,[38][39][40][41] Intra-operative complications may occur; however, these are not likely to be sight threatening. Suction loss can occur albeit the literature suggests an incidence of between 0.9 to 4.4 per cent of patients.…”
Section: Intra-operative Complicationsmentioning
confidence: 99%
“…Unsere Refraktions-sowie Visusergebnisse für beide SMILE-Gruppen sind vergleichbar mit Literaturwerten, die im Rahmen von sowohl prospektiven klinischen Studien als auch retrospektiven Analysen mit unterschiedlichen Beobachtungszeiträumen gewonnen wurden [5,6,[16][17][18][19][20][21][22][23][24][25]. So zeigten bspw.…”
Section: Diskussionunclassified
“…Numerous studies on SMILE have reported excellent outcomes; thus, the technique has gained widespread acceptance due to its efficacy, predictability, and safety [14]. …”
Section: Introductionmentioning
confidence: 99%